Avaliação da expressão gênica do receptor citotoxidade natural de células NK NKp46 e do inibidor de checkpoint imunológico CTLA-4 em pacientes com leucemia mieloide crônica tratados com diferentes inibidores de tirosina quinase - Almeida Filho, Tarcísio Paulo de (2023)
Chronic Myeloid Leukemia (CML) is a clonal myeloproliferative disease of hematopoietic stem cells. Treatment is with tyrosine kinase inhibitors (ITKs), imatinib, nilotinib, and dasatinib. The influence of ITKs on the function of T CD4+, T CD8+ and NK cells in patients with CML has been reported, however little is known about the influence of these inhibitors on specific receptors present on NK cells and T cells. Given the demonstrated importance of the immune system, especially the importance of NK cells and T cells, in the control of CML in studies of treatment discontinuation, we propose to evaluate the expression of the NKp46 gene, the most important NK cell receptor in the recognition and lysis and the expression of the CTLA-4 gene, the major negative regulator of T lymphocyte functions, in patients with different degrees of response to treatment with different ITKs and with clinical and laboratory data. This is a cross-sectional study with 71 patients with CML and a control group (CG) of 25 healthy individuals. Sociodemographic and clinical-laboratory data were obtained from medical records and gene expression was performed by qPCR. In our study, the median age of patients at diagnosis was 42 years and the CG was 29 years, we observed a higher proportion of males, 8.4% of patients had additional cytogenetic abnormalities, the b3a2 transcript was the most frequent. Regarding the influence of ITKs, patients using nilotinib showed higher expression of the NKp46 gene compared to the CG and the group using dasatinib (p<0.001; p<0.05 respectively), but there was no statistical difference with the group using imatinib (p>0.05). As for the CTLA-4 gene, there was no statistical difference between the groups. In addition, no correlation was found between the studied genes and time of use of ITKs. Patients at high risk according to the EUTOS score showed higher expression of the NKp46 gene when compared to patients at low risk (p=0.0386). For the CTLA-4 gene, the comparison between patients with and without complete cytogenetic response (CCR) showed higher levels of gene expression in patients with CCR. Furthermore, a progressive increase in CTLA-4 gene expression was observed in patients without major molecular response (RMM), with MMR and deep MR (DMR), however, only the comparison of patients without MMR and with RMP was statistically significant. The other sociodemographic and clinical-laboratory variables (gender, age, alcoholism, smoking, Sokal, Hasford and ELTS risk scores, type of transcript, karyotype and blood cell counts) did not show statistical difference. Our results also show that ≥RMM (patients with RMM and RMP) may contribute to the increase in NKp46 gene expression, at least for patients using imatinib and nilotinib. For the group using imatinib, the molecular response beyond the MMR seems not to exert an additional contribution to the expression of the NKp46 gene. For the CTLA-4 gene, we did not show statistical difference in the level of gene expression between patients with ≥RMM and GC (p=0.930), however patients without RMM had statistically lower levels of expression when compared to the CG (p=0 .0136 In short, our data show that Nilotinib is better in UP regular NKP46 expression in a chronic LMC patient, which may represent an additional beneficial effect of this medicine, since NKP46 is an important NK cell cytotoxicity receptor. In addition, we show a restoration of CTLA-4 gene expression in Patients with better RMS to ITK treatment, however no additional benefit has been noticed in patients using different ITKs. Together, these results show these markers can be regulated by ≥RMM and/or the use of nilotinib, which can mean better disease control.